Transformation of Tourism Marketing Communication Strategies through a Hybrid Approach (Online-Offline): A Case Study of The Lodge Maribaya - Indrajati Wibowo (Yayasan Pendidikan Belajar Berdikari, 2026)
This study aims to comprehensively dissect the dynamics of marketing communication strategies implemented by The Lodge Maribaya in maintaining visitor volume amidst the transition of the post-pandemic era and the massive digital disruption. The central focus of this inquiry highlights how the integration of digital marketing channels is juxtaposed with conventional approaches, specifically personal selling, particularly in targeting the corporate market segment characterized by complex decision-making processes. Adopting an interpretivist paradigm with a descriptive qualitative approach, data validity was rigorously tested using triangulation of sources and techniques, encompassing in-depth interviews with marketing policymakers, participant observation in the field, and digital footprint analysis. The analytical results indicate that The Lodge Maribaya implements an Ambidextrous Marketing strategy. In the retail segment (B2C), marketing maneuvers rely on User Generated Content (UGC) and social media virality to manufacture a Fear of Missing Out (FOMO). Conversely, for the corporate segment (B2B), the personal touch through sales visits and intensive follow-up mechanisms proves irreplaceable in mitigating client perception risks. The synergy of these two approaches is empirically capable of boosting Brand Awareness while simultaneously converting prospects into sales (Sales Conversion). These findings proffer theoretical and practical implications that digitalization does not necessarily annul the role of human interaction, especially within the hospitality industry.